Implementación del sistema integrado de gestión en la empresa de servicios TQP S.A.C para homologarse como proveedor - Zevallos Yagui, Miriam Lorena (2020)
At the present time, there is a clear trend towards the impulse of supplier homologation, which is committed to those companies that obtain certification and exclude those that do not comply with any essential norm. For this reason, TQP S.A.C. takes the initiative to obtain the Certification of Homologation of Suppliers, which allows it to be a reliable company, which would make it easier for customers to make the decision when contracting their services. With a Quality Management System, Occupational Health and Safety Management System, and Environmental Management System implemented, he applied a first homologation, the results of which were not what he expected. In addition, having difficulties caused by operational shutdowns due to customer observations, it considers the need for integrated management, being the implementation of the Integrated Management System, a strategy of greater level of competitiveness and the timely response to the problematic you have at that time. Because TQP S.A.C. It has its systems that act independently, it is essential to review some aspects and make them compatible with the structure of the Integrated Management System; In this way, it would be breaking down the barrier that prevents it from obtaining the homologation certificate and fulfilling its corporate objectives. The phases considered are adapted to the PDCA cycle and comply with the requirements focused on International Standards. In addition, actions are shown to ensure that the Integrated Management System remains in force, updated, active, dynamic and faces the challenge of continually improving.